Undergraduates Research Interest: Study Based on Bachelor of Commerce Undergraduates of University of Sri Jayewardenepura - Sachitra, K.M.V. (University of Sri Jayewardenepura, Nugegoda, 2016)
Research in study programmes has become essential to the modern tertiary education, especially in management studies. The present market demands at least minimum research competencies in order to face the technological and human resource challenges. In recent times, it has been identified that undergraduates’ interest towards engaging in research studies is getting declined. Thus, the main intention of the study is to investigate the effect of beliefs, self-efficacy, attitudes, and motivation on undergraduates' interests in doing research. One hundred and eighty undergraduates from the Department of Commerce who had completed the research methodology course unit participated in the study by way of answering a structured questionnaire. Undergraduates’ responses were analyzed through mean comparisons. The results indicate that undergraduates believe that engaging in research is stressful, complicated and a difficult task; and it was observed that generally they have a negative attitude towards conducting research. Since they possess knowledge and skill required to perform research, English language barrier and lack of academic support need to be addressed in promoting research among them.
Keywords: Attitudes; Beliefs; Mean Comparison; Motivation; Self-efficacy; Undergraduate Research